Infiltrasi Petroleum Hydrocarbon pada Air Sumur Gali di Jalan X Kecamatan Gresik - Hasti Suprihatin; M. Asrin; Akhmad Andi Saputra; Ikhtisholiyah (Fakultas Teknik Universitas Muhammadiyah Parepare, 2026)
Groundwater obtained from dug wells serves as the main domestic water source for communities along Jalan X, Kecamatan Gresik. Recently, oil contamination detected in several wells has raised significant environmental and public health concerns, while the pollution source has not been clearly identified. This study aims to assess Total Petroleum Hydrocarbon or TPH concentrations in dug well water and to determine the primary source of contamination. A case study with a descriptive quantitative approach was conducted through field observations and laboratory analysis of groundwater samples from three affected wells. TPH levels were measured using gas chromatography–flame ionization detector or GC-FID and evaluated against drinking water quality standards established by the Indonesian Ministry of Health Regulation No. 32 of 2017. The results showed TPH concentrations up to 2.5 mg/L, exceeding the safe drinking water threshold by 25-fold. The major finding identifies the contamination source as a leaking domestic drainage channel located only six meters from the wells, which violates the standard safe distance. This channel carries hydrocarbon waste from adjacent vehicle workshops, infiltrating the shallow aquifer. Therefore, immediate reconstruction of the drainage using pre-cast U-ditch and provision of a piped water system are necessary to protect community health.